MATHEMATICAL DIFFICULTIES LEARNERS IN SOLVING CREATIVE THINKING IN THE GEOMETRY ABILITY - Depi Setialesmana (STKIP Singkawang, 2017)
The purpose of this study to identify the Difficulties and disadvantages experience by learners in terms of the process of settlement problems of mathematical creative thinking abilities part of indicators. The research instrument used was a matter of mathematics creative thinking ability test and interview guidelines Subject in this study in class VIII-D Junior High School. Based on the research results, Difficulties and disadvantages experienced by learners when solving test creative thinking abilities mathematics include, most learners do not express a variety of ideas, ideas or plans of settlement diverse, does not solve the problem in various ways, does not try to solve problems in ways own or use a non-standard way, and most learners do not develop and elaborate the answer in solving problems.